Reviu Implementasi Program 8 Aksi Percepatan Penurunan Stunting di Kabupaten Tangerang Provinsi Banten Tahun 2022 - Maharani, Enziana; Ahmad Syafiq (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine the implementation of the 8 Stunting Reduction Acceleration Actions program in Tangerang Regency, Banten Province in 2022. This program is a national initiative that aims to reduce the prevalence of stunting through a convergence approach, cross-sector integration, and community participation. This study uses a qualitative method with a Public Health Nutrition (PHN) cycle approach which includes stages of intelligence, action, and evaluation. Data was collected through in-depth interviews with informants from Regional Apparatus Organizations (OPD) and review of related policy documents. The results show that the implementation of the 8 actions has been quite effective, but there are still challenges in cross-sector coordination and continuous monitoring. Action 1 (Situation Analysis) and Action 7 (Measurement and Publication of Stunting Data) are crucial stages in determining priority villages and measuring program achievements. However, action 8 (Annual Performance Review) has not been fully implemented consistently. The study provides recommendations to strengthen coordination between OPDs, increase human resource capacity, and ensure the sustainability of interventions through integrated and sustainable planning. This research is expected to contribute to the development of public health policies at the local level and accelerate the achievement of stunting reduction targets nationally.